Analisis Penggunaan Media Pembelajaran Berbasis Game terhadap Pemahaman Konsep Pendidikan Pancasila Kelas IV - Suci Anis Kunaifi; Heru Purnomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Learning using interactive media has been widely applied in various elementary schools. This study was conducted to determine the success of using game-based learning media on the understanding of the concept of Pancasila Education in class IVA students at SD N Meijing 2. This study is a descriptive qualitative study. Then the approach used is a descriptive approach through the results of interviews, observations, and documentation. The subjects of this study were class IVA teachers of SD N Meijing 2 and class IVA students of SD N Meijing 2 with a total of 28 students. The results of the study concluded that learning activities using game-based media greatly influenced the understanding of the concept of Pancasila Education in class IVA students of SD N Meijing 2. Through game-based media, students are more enthusiastic and interested in participating in learning activities because they feel it is easier to understand the material being taught.